New Palaeolithic and Mesolithic sites in the eastern Aegean: the Karaburun Archaeological Survey Project. (15th September 2016) - Çilingiroğlu, Ç.; Dinçer, B.; Uhri, A.; Gürbıyık, C.; Baykara, İ.; Çakırlar, C.
Abstract : Despite ongoing fieldwork focusing on the Palaeolithic and Mesolithic periods of the Aegean, the eastern part of this region, especially western Turkey, remains almost entirely unexplored in terms of early prehistory. There is virtually no evidence from this area that can contribute to broader research themes such as the dispersal of early hominins, the distribution of Early Holocene foragers and early forager-farmer interactions. The primary aim of the Karaburun Archaeological Survey Project is to address this situation by collecting data from the eastern side of the Aegean Sea, thereby contributing to the currently debated issues of Aegean and Eastern Mediterranean prehistory.